2018
DOI: 10.1111/cdev.13078
|View full text |Cite
|
Sign up to set email alerts
|

Children's Vulnerability to Interparental Conflict: The Protective Role of Sibling Relationship Quality

Abstract: This study tested whether the strength of the mediational pathway involving interparental conflict, adolescent emotional insecurity, and their psychological problems depended on the quality of their sibling relationships. Using a multimethod approach, 236 adolescents (M = 12.6 years) and their parents participated in three annual measurement occasions. Tests of moderated mediation revealed that indirect paths among interparental conflict, insecurity, and psychological problems were significant for teens with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 63 publications
3
32
0
Order By: Relevance
“…This aligns with previous research conducted during disaster situations (e.g., hurricane, tsunami), according to which positive family relationships serve to reduce mental health symptoms (e.g., depression, PTSD) among children ( Wickrama and Kaspar, 2007 ; Kronenberg et al, 2010 ). Further, the presence of a positive relationship with even one family member has been shown to be enough to buffer the negative impacts of psychological distress caused by unfavorable circumstances ( Vakrat et al, 2018 ; Davies et al, 2019 ). In the context of COVID-19, family functioning is especially important to consider as many families are spending a greater amount of time together due to preventative policies, such as social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with previous research conducted during disaster situations (e.g., hurricane, tsunami), according to which positive family relationships serve to reduce mental health symptoms (e.g., depression, PTSD) among children ( Wickrama and Kaspar, 2007 ; Kronenberg et al, 2010 ). Further, the presence of a positive relationship with even one family member has been shown to be enough to buffer the negative impacts of psychological distress caused by unfavorable circumstances ( Vakrat et al, 2018 ; Davies et al, 2019 ). In the context of COVID-19, family functioning is especially important to consider as many families are spending a greater amount of time together due to preventative policies, such as social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Given that sibling relationships have been established as a potential resource against negative developmental outcomes (e.g., Buist & Vermande, ; Davies et al, ), this study was the first to test whether perceived sibling support could moderate the intergenerational transmission of observed romantic relationship hostility. Many studies rely on retrospective cross‐sectional designs and single reporters to examine the associations between varying relationship dynamics (Reese‐Weber & Kahn, ); however, the current study used a range of methods in a prospective longitudinal design to reduce rater bias and confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…One untapped family resource is sibling relationships, which can provide a salient source of support for responding to negative life events (Kramer, Conger, Rogers, & Ravindran, ), such as family stress (K. J. Conger, Stocker, & McGuire, ). For instance, perceiving supportive behavior from siblings can dampen the association between hostile home environments and adolescent externalizing and internalizing problems (Davies, Parry, Bascoe, Martin, & Cummings, ). Furthermore, the malleability of sibling relations has provided an excellent point of intervention for improving child responses to negative family dynamics, such that sibling‐focused interventions associate with better child emotion regulation and social skills, as well as sibling relationship quality (Feinberg et al, ; Kennedy & Kramer, ; C. J. Tucker & Finkelhor, ) These findings suggest that perceptions of sibling relations may be a protective factor against transmitting hostile family dynamics.…”
mentioning
confidence: 99%
“…In general, findings support the family systems spillover hypothesis (Engfer, 1988; Repetti, 1987) in that marital conflict is associated with conflict in the sibling relationships, and marital warmth is linked to positive sibling relationships (Kim, McHale, Osgood, & Crouter, 2006; Stocker, Ahmed, & Stall, 1997). In contrast, some research has found that warm and supportive sibling relationships can protect children from the negative impact of their parents' marital conflict (Davies, Parry, Bascoe, Martin, & Cummings, 2019; Gass, Jenkins, & Dunn, 2007). It is unclear whether these patterns continue into adulthood.…”
Section: Review Of Current Knowledge On Sibling Relationships In Adulmentioning
confidence: 99%